Metaverse cannot be an extra marketing immersive tool to increase sales in tourism cities - Florido Benítez, Lázaro (Emerald, 2024)
The purpose of this paper is to analyse the metaverse platform in a social context to better understand the future of this tool in tourism cities and how this can help to improve the well-being of residents in both digital and physical scenarios.
Keywords: Turismo; Población urbana; Minusválidos; Metaverse; Tourism cities; Residents; Tourists; People with disabilities